Irish Officers in the British Forces, 1922-45 - O'Connor, Steven. author. aut Link
XV, 249 p.
Keywords: Irish Officers in the British forces, 1922-45 looks at the reasons why young Irish people took the king's commission, including the family tradition, the school influence and the employment motive. It explores their subsequent experiences in the forces and the responses in independent Ireland to the continuation of this British military connection.